Social Network Patterns of Creative Economy Actors in the Culinary Sector of Tourism Destination Areas in Padang City West Sumatra - Lubis, Gebi Cahyani; Zusmelia, Zusmelia; Irwan, Irwan; Scurtu, Ionut Cristian (LPPM Universitas PGRI Sumatera Barat, 2024)
This research was conducted to analyze the network patterns of creative economy actors in the culinary sector in Padang City. Data collection methods in this study began with documentation studies, in-depth interviews and non-participant observation. The approach used in this research is a qualitative approach with a descriptive analytical type and the withdrawal of informants through purposive sampling and snowball to see the relationship between creative economic actors in the culinary sector. The unit of analysis in this study is the individual. The results of this study indicate that creative economic actors in the culinary sector in Padang City have been able to build social networks. This can be seen in the distribution of culinary products that have been carried out by creative economic actors in the culinary sector outside the Padang City area. The social network pattern formed in the creative economic actors in the culinary sector is in a mixed social network pattern. In addition, creative economic actors build social network patterns in 4 forms, namely family-based social network patterns, friendships, joint activities and social media and customers. The social network pattern is spread in the distribution of culinary products that have been created and provides information on the acquisition of raw materials, strategies in product marketing and the results of product profits obtained by creative economic actors in the culinary sector. The novelty of this research is a mixed-based social network pattern.